Effects of operating conditions and geometries on the performance of nitrogen ejectors for Joule–Thomson cooling. (25th July 2022) - Geng, Lihong; Cao, Haishan; Meng, Qinghang; Li, Junming; Jiang, Peixue
Abstract: Ejectors in Joule–Thomson (JT) cooling cycles can reduce the evaporator pressure and the compressor power consumption, achieving lower temperatures and higher efficiencies. The ejector, being a major component of a JT cooling cycle with an ejector, is critical to overall cooling performance. In this study, the effects of inlet pressures, outlet pressures, inlet temperatures, nozzle, and mixing geometries on the performance of nitrogen ejectors are investigated experimentally and numerically. The critical back pressure of the ejector increases as the primary and secondary inlet pressures increase. Depending on the working mode, the entrainment ratio varies with the ejector inlet temperature. The clogging due to the deposition of water molecules as impurities occurs when the ejector inlet temperature is below 222 K, resulting in the rapid reduction of mass-flow rates. For nitrogen ejector designs, the following ratios are recommended: constant-area mixing chamber diameter to nozzle outlet diameter, constant-area mixing chamber diameter to nozzle throat diameter, nozzle exit position to constant-area mixing chamber diameter, constant-area mixing chamber length to constant-area mixing chamber diameter. The results of this study will be beneficial in promoting the use of ejectors in JT cooling cycles. Highlights: Ejector performance is studied in relation to operating conditions and geometries. Two ejectors with nozzle throat diameters of 155 μ m and 182 μ m are built and tested. Clogging phenomenon in ejectors is observed at temperatures below 222 K. Variation in entrainment ratio with temperature depends on ejector working mode.